Tandem radical cyclization of N-methacryloyl benzamides with CBr4 to construct brominated isoquinolinediones. Issue 41 (9th October 2018) - Huang, Songhai; Niu, Pengfei; Su, Yingpeng; Hu, Dongcheng; Huo, Congde
Abstract : Cumene promoted auto-oxidation involved tandem radical cyclization of N -methacryloyl benzamides using CBr4 as the bromine source to construct brominated isoquinolinediones is described. Abstract : A simple cumene (isopropylbenzene, IPB) promoted auto-oxidation involved tandem radical cyclization of N -methacryloyl benzamides using stable and easy-to-handle CBr4 as the bromine source is described. This strategy provides an efficient and practical approach for the synthesis of bromine containing isoquinolinediones. This method also presents a new way to generate bromine radicals using a mild auto-oxidation pathway.